(untitled) (Journal of the Sociology and Theory of Religion, 2026)
This essay explores St. Augustine of Hippo’s enduring influence on Western Christianity, contextualized within the 1700th anniversary of the Nicene Council (325–2025). Augustine’s theology, shaped by his encounters with Manichaeism, Platonism, and Christian orthodoxy, provided foundational principles for the Society of Jesus (Jesuits), founded in 1540. The essay examines Augustine’s doctrines of grace, original sin, and sacramental theology, which resonate with the Nicene Creed’s affirmation of Christ’s divinity and the Church’s universality. It also investigates the Jesuits’ reliance on early Christian theologians like Ignatius of Antioch, Origen, and Tertullian, whose emphases on spiritual discipline, intellectual rigor, and apologetics informed Jesuit spirituality and mission. By tracing these theological roots, the essay argues that Augustine’s practical and introspective approach, combined with the missionary and scholarly zeal of other patristic figures, shaped the Jesuits’ role in the Counter-Reformation and beyond.